A spatio-temporal delineation of trans-boundary ecosystem service flows from Inner Mongolia. (24th May 2019) - Xie, Gaodi; Liu, Jingya; Xu, Jie; Xiao, Yu; Zhen, Lin; Zhang, Changshun; Wang, Yangyang; Qin, Keyu; Gan, Shuang; Jiang, Yuan
Abstract: Ecosystem service (ES) flows across geophysical and administrative boundaries are ubiquitous and are receiving more attention in an increasingly metacoupled world. Omitting trans-boundary ES flows from ES assessments will lead to unilateral conclusions and underestimation of ES contributions over distances. Inner Mongolia is an important ecological security barrier of China and Eurasia, but the trans-boundary effect of this barrier is difficult to be quantitatively evaluated and is rarely assessed. This study assessed the ecological security barrier function of Inner Mongolia from the perspective of trans-boundary ES flows, including wind prevention and sand fixation (WPSF), water provision (WP), carbon sequestration (CS) and livestock product provision (LPP) service flows. The trans-boundary value flows for the WPSF, WP, CS and LPP services in 2010 were 6.20 × 10 10 CNY (Chinese currency, yuan), 0.21 × 10 10 CNY, 1.29 × 10 10 CNY and 1.27 × 10 10 CNY, respectively, and 5.89 × 10 10 CNY, 0.16 × 10 10 CNY, 0.37 × 10 10 CNY and 1.33 × 10 10 CNY, respectively, in 2015; correspondingly, the percentages of these trans-boundary value flows in terms of the total value flow were 69.12%, 2.34%, 14.38% and 14.16%, respectively, in 2010 and 76.00%, 2.06%, 4.77% and 17.16%, respectively, in 2015. Therefore, WPSF service plays a more important role in the trans-boundary ecological security barrier function of Inner Mongolia. This study can enhance the understanding of trans-boundary telecoupling in an integral socio-ecological system and identify the critical ESs to form a foundation for ecological conservation measures considering sustainable development.